Husein Muhammad’s Thoughts on Gender Equality in Islamic Inheritance Law - Firdawaty, Linda; Munji, Ahmad; Sukandi, Ahmad; Bukhari, Nurnazli; Apriani, Ira (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to analyze the philosophical reasons for Husein Muhammad's thoughts about the importance of the equal distribution of inheritance between men and women in Islamic inheritance law, as well as the method of legal reform that he uses when understanding verses about inheritance. This research is field research. Data was collected through virtual interviews. Data analysis was descriptive qualitative, with maslahah theory, and historical and sociological approaches. The research findings show that one of the reasons why verses about inheritance need to be reinterpreted, according to Husein, is because these verses fall into the category of mutashabihat verses (interpretable) so they need to be reinterpreted by looking at the current context. Another reason is that the inheritance verses that regulate section 2:1 for men and women in the Prophet's era were only intended for the context of society at that time, where women had no inheritance rights, and even women were used as objects of inheritance. Nowadays, the existence of women is growing. That way the portion of their inheritance should be reformed and adapted to current socio-cultural developments. Husein emphasized that gender bias occurs due to bias when interpreting the Qur’an, and the influence of patriarchal culture.